Estimate the Serum Level of IL-17A and TGF-?1 1 in Iraqi Generalized Vitiligo Patients - Shatha F. Tariq (Institute of Medico-legal Publications Pvt Ltd, 2020)
Vitiligo is an acquired idiopathic skin disease characterized by white macules result from the destruction ofmelanocytes. Several cytokines have been implicated in the pathogenesis of vitiligo, keeping this in viewthe current study aimed to evaluate the serum levels of IL-17A and TGF-?1 in 25 patients with generalizedvitiligo and compared them with healthy individuals in order to investigate whether these cytokinesimbalances plays a role in the pathogenesis of this depigmentary disorder. Results of the present studyshowed that the serum level of IL-17A in vitiligo patients was increased significantly (p? 0.05) while theserum level of TGF-?1 was decreased significantly (p? 0.05) as compared with healthy control. Accordingto the gender of patients, males had a slightly non-significant increased (p<0.05) in the level of IL-17A andTGF-?1 as compared with females. Patients with early onset vitiligo had non-significant increased (p<0.05)in the level of IL-17A and TGF-?1 as compared with late onset vitiligo patients. No significant differences(p<0.05) were detected in the levels of IL-17A and TGF-?1 in patients regarding the clinical types of vitiligo,family history and Koebner phenomenon. Patients with active disease had a significant increase (p?0.05) inthe level of IL-17A, though a significant decrease (p?0.05) in the level of TGF-?1 was noticed as comparedwith both patients with stable disease and healthy control groups. Serum levels of both IL-17A and TGF-?1have been shown to be negatively correlated with the disease duration (r=-0.174, p=0.405) and (r=-0.057,p=0.788) respectively